Risk assessment for safety and health algorithm for building construction in Oman - Al-Anbari, Saud Said (2015)
Building construction is extremely hazardous. Numerous fatal and non-fatal vocational injuries occur due to the unique nature of the building construction workplace. The swift expansion of the Omani economy has led to the extensive expansion of infrastructure and resources in the construction sector. Hazard Identification, Risk Assessment and Risk Control (HIRARC) is a structured approach for identifying, evaluating and controlling hazards in the work place. Risk assessment matrices are widely used to evaluate risks related to such hazards. Existing risk matrices are designed based on brainstorming sessions, which may make these matrices risky to use because such sessions are based mainly on experience and knowledge about the decision at hand. The general objective of this study is to carry out a Risk Assessment for Safety and Health (RASH) algorithm for building construction in Oman and to develop a calculation methodology to evaluate safety and health. The RASH algorithm is defined by overall risk, which is equivalent to the sum of Risk Safety Safety, Risk Safety Health, Risk Health Safety, and Risk Health Health. By implementing definitions of safety and health on the identified extreme and high-risk levels, the key risks in this study have been classified into safety risks and health risks. Then, the safety risks have been categorized into 11 factors, and the health risks have been categorized into 8 factors. Using these two categories of risk, four scenarios reflecting the four zones of the occupational safety and health risk matrix were designed. Then, 40 safety and health specialists were involved in carrying out a risk assessment using the existing method of risk analysis (RA) and the new proposed method of RASH. The Wilcockson Ranked Test was applied to evaluate the differences between these two methods. It was found that there were differences between the percentages of correct answers found by the two methods, as follows: 75% of RASH answers were correct, and 40% of RA answers were correct. The results revealed that the two methods are significantly different (z=0.357, p > 0.01). It was also found that RA respondents tend to overestimate risk, even when conditions were very safe. This common mistake has cost and time implications in construction activities. It was found that 60% of evaluations using RA might be estimated mistakenly. From the analysed results, it is recommended that organizations refrain from relying on the RA to prepare risk assessments and mitigation plans. Instead, it is suggested that results be verified with an alternative method of assessing risk, such as RASH. In conclusion, RASH is an alternative and effective method for the assessment of safety and health risks in building construction in Oman.